Cost Function for Sound Source Localization with Arbitrary Microphone Arrays - Tashev, Ivan; Le, Long; Gopalakrishna, Vani; Lovitt, Andrew (Proc. HSCMA, 2017)
The sound source localizer is an important part of any microphone array processing block. Its major purpose is to determine the direction of arrival of the sound source and let a beamformer aim its beam towards this direction. In addition, the direction of arrival can be used for meetings diarization, pointing a camera, sound source separation. Multiple algorithms and approaches exist, targeting different settings and microphone arrays. In this paper we treat the sound source localizer as a classifier and use as features the phase differences and magnitude proportions in the microphone channels. To determine the proper mix, we propose a novel cost function to measure the localization capability. The resulting algorithm is fast and suitable for real–time implementations. It works well with different microphone array geometries with both omnidirectional and unidirectional microphones.